With Beatty off Jutland: A Romance of the Great Sea Fight - Westerman, Percy F. (Percy Francis), 1876-1959; Gillett, Frank, 1874-1927 (Salt Lake City, UT : Project Gutenberg, 2012)
"With Beatty off Jutland: A Romance of the Great Sea Fight" by Percy F. Westerman is a historical novel written in the early 20th century. This work immerses readers in the naval battles of World War I, focusing on the crew of the British destroyer H.M.S. "Calder," particularly Acting Sub-lieutenant Jack Sefton as they undertake risky submarine operations in the North Sea. Themes of courage, camaraderie, and the brutal realities of warfare are prominent throughout the narrative. The opening of the narrative introduces the cold, tense atmosphere aboard H.M.S. "Calder." As she and her crew engage in a high-stakes mission to locate a crucial undersea cable, Sub-lieutenant Sefton and his fellow officers navigate their responsibilities while maintaining a light-hearted camaraderie. The piece paints a picture of the daily life aboard the destroyer, filled with both mundane duties and the constant threat of enemy engagement. Tension builds as they finally hook the cable they$1 (Bre after, leading into the promise of further action and conflict on the horizon. The stage is set for a thrilling tale of naval warfare and adventure on the open sea. (This is an automatically generated summary.)s
Release date is 2012-04-19
Produced by Al Haines
Keywords: Great Britain. Royal Navy -- Juvenile fiction; World War, 1914-1918 -- Naval operations -- Juvenile fiction; Jutland, Battle of, 1916 -- Juvenile fiction